Impact of international non-governmental organisations (Ingos) on youth development in Yobe State, Nigeria - Abdullahi, Muhammad (2020)
The ongoing crises in North-East region of Nigeria attracted many international nongovernmental organisations (INGOs) to come into the country with different forms of assistance ranging from emergency support to development based interventions for the benefit of people living in the region. These assistances are directly or indirectly affecting the lives of all categories of people living in the region. It is against this backdrop that this study assessed the impact of INGOs on youth development in Yobe State, Nigeria; with specific emphasis on social, economic and political spheres among youths. The study was survey research that utilised virtual structured questionnaires to generate information from respondents. Convenience sampling technique was utilised in generating 394 responses. The study revealed that INGOs certainly impacted on the lives of youths, especially in the areas of employment and skill acquisition opportunities, education, healthcare and youthful female empowerment. The study recommended that governments create enabling environment for INGOs to operate with very close monitoring of their operations, and ensure that indigenous populations are largely employed by the organisations.